Trends in United States Family Forest Owners’ Attitudes, Behaviors, and General Characteristics from 2006 to 2018 - Emma M Sass; Brett J Butler; Jesse Caputo; Emily S Huff (Forest Science, 2023)
Family forest owners (FFOs) control a plurality of forestland in the United States, and the decisions these landowners make have a profound impact on the landscape. Most research on FFOs consists of cross-sectional studies, although many of these recognize the importance of capturing long-term trends to understand whether and how FFO attitudes, behaviors, and general characteristics are changing. We use data from the 2006, 2013, and 2018 iterations of the USDA Forest Service, National Woodland Owner Survey (NWOS), with a bootstrapping approach to identify significant changes across these time periods among FFOs with 4+ hectares of forestland. Total FFO hectares decreased and FFO ownerships trended downward over the study period. A decreasing proportion of FFOs owned farms or homes near their forestland, harvested timber, or received advice. Demographic shifts include an increase in age and education level from 2006 to 2018, and an increase in FFOs of color from 2006 to 2013. Overall, we find a trend towards decreased traditional engagement and management and a slight increase in owning land for its amenity values. Understanding temporal trends in FFO characteristics, attitudes, and behaviors will help policymakers and forestry professionals inform and update their outreach, technical support, and financial assistance programs. Study Implications: Families and individuals hold more forestland than any other ownership group in the United States. We use nationwide survey data from 2006, 2013, and 2018 to determine whether and how these landowners are changing over time. The total forestland held by FFOs decreased between 2006 and 2018, and there has been a decrease in traditional forest management and engagement, such as through timber harvesting and nearby farm ownership. This study provides insights for policies, programs, and outreach and a foundation for future long-term comparisons of this group.